Successful Endovascular Management of Resistant Hypertension Post Kidney Transplant: A Case Report. (September 2022) - Madken, Mohit; Gotra, Akshat; Qazi, Shakeel; Fairhead, Todd; Burns, Kevin D.
Rationale: Transplant renal artery stenosis (TRAS) is a well-recognized and potentially reversible cause of resistant hypertension post transplantation and can affect 1% to 23% of recipients. Stenosis of the iliac segment proximal to the transplant renal artery (proximal TRAS) causing dysfunction of the transplanted kidney is less common with reported incidence of 2% to 3%. Presentation typically occurs between 3 months and 2 years post transplant but may happen at any time. Noninvasive investigations such as Doppler ultrasound, computed tomography (CT) angiogram, and magnetic resonance angiogram are useful in initial evaluation, but definitive diagnosis of hemodynamically significant stenosis often requires formal angiogram. Transplant renal artery stenosis should be suspected in any kidney transplant recipient with worsening hypertension and/or deterioration in kidney function which is otherwise unexplained. We present the case of a kidney transplant recipient with resistant hypertension and impaired graft function, secondary to severe impairment of graft blood flow from proximal iliac system occlusion. Presenting concerns of the patient: A 74-year-old female 15 years post live donor kidney transplant presented with graft dysfunction (serum Cr 229 μmol/L) and resistant hypertension, requiring use of 8 antihypertensive medications. On physical examination, blood pressure was 160/92 mm Hg with no tenderness over the renal graft in the right lower abdominal quadrant and no audible bruit in kidney allograft area. Diagnosis: Transplant Doppler ultrasound showed reversal of flow in the right external iliac artery suggestive of ipsilateral proximal iliac occlusion. Pre-procedure CT demonstrated severe atherosclerotic burden within the aorta and bilateral iliac systems. The anastomosed right renal artery appeared patent. Interventions: Conventional angiogram showed occlusion of the right common and proximal external iliac arteries with retrograde perfusion of the transplant kidney via the contralateral left iliac system and aorta. Subintimal recanalization of the right iliac system was performed with angioplasty and kissing stent placement at the aortic bifurcation with stents extending into the proximal right external iliac artery. Post deployment angiogram demonstrated renewed patency of the right iliac system, with restoration of antegrade perfusion to the transplant kidney. Outcomes: The patient's blood pressure decreased significantly after the procedure, with improvement in graft function. After 6 months, the patient continued to have optimally controlled blood pressure (on 3 medications) and stable graft function (serum Cr 74 μmol/L). Teaching points: Our case describes proximal TRAS and the contribution of renal hypoperfusion to hypertension and impaired graft function, with the potential for reversibility.